Peran Strategis Indonesia dalam Geopolitik Transisi Energi di Bidang Sumber Daya Mineral - Dini Putri Saraswati; Shanti Darmastuti; Nurfarah Nidatya; Dinda Jasmine (Pusat Riset dan Inovasi Nasional, 2025)
The global energy transition, marked by a shift from fossil fuels to renewable energy, reflects a major transformation in the structure of global geopolitical power. Indonesia plays a strategic role in this process through its reserves of critical minerals such as nickel and copper, which are essential components in clean energy technologies, including electric vehicles and solar panels. This study aims to analyze Indonesia’s role in the global clean energy supply chain using the approaches of geopolitical economy and resource nationalism. These approaches allow for a deeper understanding of the dynamics of identity, sovereignty, and the distribution of benefits within global resource contestation. A qualitative method is employed with a naturalistic approach and literature review to interpret Indonesia’s policies, geopolitical position, and mineral resource utilization in a contextual manner. The analysis reveals that while Indonesia holds significant bargaining power as a key supplier, it still faces major challenges in the form of regulatory gaps, environmental risks, and pressure from the global trade system. The findings imply the need for stronger resource governance, economic diplomacy, and cross-sector policy integration to ensure that Indonesia can optimally play its role in the global energy transition.